Exploring the Relationship of School Climate, Life Satisfaction and Empathy in Costa Rican Adolescents - Alvarado Calderón, Kathia (2021)
An assessment of the relationship existing among life satisfaction, empathic response and school climate, based on a perception of five aspects, was conducted among 401 student participants between the ages of 15-17. This was a correlational study based on the use of three self-administered questionnaires: Huebner's SLSS (Student Life Satisfaction Scale), the Aron and Milicic School Climate Questionnaire and the Interpersonal Reactivity Index (IRI). Non-parametric statistical analysis revealed no significant differences according to age in any of the areas studied. Significant gender differences were observed in the Interpersonal Reactivity Index. Empathic response, satisfaction with life and perception of school climate were associated positively. Bullying was not associated with any of the aspects of the study. All of the questionnaires had good reliability values. It concludes on the importance of continuing to study school social climates in relation to the empathic response and satisfaction with life to promote healthy environments. Teachers play a relevant role in assessing satisfactory school climates, infrastructure conditions and extracurricular activities available to the student community. More programs to promote social skills in educational contexts are necessary for gender mainstreaming and foster genuine concern for the pain of the other, an affective response that shows empathy and is frequently associated with female traits.